Practicalities of community-led continuous water quality monitoring: lessons from Taiwan and UK pilots - Starkey, Eleanor; Jones, Amy; Ochoa-Rodriguez, Susana; Mahajan, Sachit; Wei, Chi-Ling; Chen, Pei-Chun; Liu, Shau-Yuan; Wang, Li-Pen; Walsh, Claire L. (Frontiers in Environmental Science, 2024)
Freshwater pollution is a global challenge that citizens recognise as unacceptable, despite professional efforts to monitor, manage, and regulate it. Water quality is difficult to observe at high spatial and temporal resolutions; it is costly and typically requires trained specialists in the field and in laboratories. However, the rise in citizen science monitoring has generated opportunities to overcome many barriers and fill data gaps. Citizens want access to actionable water quality information that can provide early warnings and drive change. Our bibliographic analysis emphasises that citizen science is rarely paired with the use of continuous sensors, and many monitoring schemes involving the public are unable to offer the detail required. This study has explored the practicalities and competencies associated with community-led (near) continuous water quality monitoring (CWQM), and has generated an extensive checklist containing technical, social, economic, and wider responsibilities that stakeholders should consider. The ‘UpStream’ project has provided a testbed for this exploratory work and the development and deployment of the ‘WaterBox’ CWQM device. Case studies from the UK and Taiwan, where community-led CWQM programmes have been piloted, have provided novel methodological insights. Lessons learnt have enabled researchers to determine whether, and to what extent, community-led CWQM is achievable in practice. Results confirm that 75% of the practicalities observed fall under the ‘technical’ category, despite offering a social and inclusive methodology. Through observational work, it was found that only 34% of the 104 practicalities were led by community groups and community champions. Communities require significant support owing to the sheer number of technical barriers, although some of this could be provided by skilled community champions. These findings have surfaced despite the WaterBox equipment being open, accessible, cost-effective, and adaptable. Unless support is in place and/or technology significantly evolves to reduce the number of challenges, it is unlikely that communities will lead and take full ownership of CWQM programmes. Despite this, the generation of site-specific CWQM data are welcomed by citizens, who can co-design schemes, interpret trends and offer valuable local information that trained scientists cannot achieve alone. These transferable findings are relevant to monitoring initiatives across the environmental sector.